Analysis of The Financing Activities of The Iraqi Housing Fund and Its Role in Supporting The National Economy: An Applied Study in The Housing Fund\ Diyala Branch - Mohammed, Thaer Saadoon; Abdullah, Luay Qays; Abdullah, Luay Qays (International Journal of Psychosocial Rehabilitation, 2020)
The present research studies the role of the housing fund and its role in financing the housing sector in Iraq by analyzing the fund’s financing activities for the period from 2005 to 2017, as the research problem was represented in the level of meeting the housing sector requirements in Iraq, and the annual economic bulletins issued by the Central Bank of Iraq and the Housing Fund were used. To collect data, data were analyzed using analysis tables. The research reaches a set of conclusions, the most important of which was the increase in the activities of the Housing Fund in providing financing after 2012, in order to grant loans without interest, but it is still below the level of ambition to meet the requirements of the housing sector in Iraq. The research ends with a set of recommendations, including finding new and innovative financing tools. It contributes to providing financing for projects that produce housing units with high speed and flexibility, such as increasing the ceiling for loans to high-income segments, and granting loans according to completion rates.